Atmospheric Dust Variations in the Ili Basin, Northwest China, During the Last Glacial Period as Revealed by a High Mountain Loess‐Paleosol Sequence. Issue 15 (2nd August 2019) - Li, Yue; Song, Yougui; Qiang, Mingrui; Miao, Yunfa; Zeng, Mengxiu
Abstract: Atmospheric dust emission is closely related to conditions in the source area. Typically, loess deposits represent the accumulation of locally derived dust, providing the opportunity to reconstruct past variations in dust emission and hence insights into dust‐climate linkages and the underlying mechanisms of dust mobilization, transport, and deposition. As yet, however, information on patterns of dust emission in Central Asia is sparse. Here we present the last glacial sedimentological data of a loess section from the Ili Basin, northwest China. Our results show that the variations in sand‐sized fraction can indicate frequencies of occurring strong winds, which was likely driven by the Eurasian ice sheets during Marine Isotope Stage Stage 2 (MIS2) and MIS4 and by the boreal summer insolation during MIS3. The mass accumulation rate (MAR) reflects an integration of sediment availability in the provenance, vegetation cover in the deposition area, and wind regime. The differences of driving factors potentially explain the observed mismatches between variations in grain size and MAR. Comparison of dust fluxes observed in Greenland ice core and the North Pacific deep‐sea sediment with the Central/East Asian MAR records supports the idea that the high flux of long‐distance export of Asian dust is closely associated with the Siberian High and also influenced by changes in the atmospheric transport efficiency and likely by the source strength. Key Points: Eurasian ice volume was crucial for the eolian processes in the Ili Basin Mismatches between the grain size and MAR variations lie in differences in their governing factors Climate of source regions and transport efficiency modulated dustiness in the Ili Basin and dust flux in distant paleoarchives